Effects of the 11+ and Harmoknee warm-up programs on physical performance measures in professional soccer players - Daneshjoo, A.; Halim Mokhtar, A.; Rahnama, N.; Yusof, A. (Journal of Sports Science & Medicine, 2013)
The purpose of this study was to examine the effects of the 11+ and HarmoKnee warm-up programs on performance measures in professional soccer players. Thirty-six male professional soccer players (age: 18.9 ± 1.4 years) were divided into 3 groups, the 11+, HarmoKnee and control group (n = 12 per group). The experimental groups performed the programs 3 times per week for 2 months (24 sessions), whereas the control group only performed their regular soccer training. The performance tests carried out were: 10m speed tests with and without a ball, 20m single sprint, vertical jump, Wall-Volley and Illinois agility tests. The 11+ group demonstrated significant increases from pre-to-post time points in the vertical jump (3.7%), Wall-Volley (5.4%) and Illinois agility tests (1.7%), while the HarmoKnee group showed a significant increase in Wall-Volley test, with a 5.2% increase. The repeated measures analysis revealed differences between the groups (large effect size) in the 11+ and HarmoKnee groups, compared to the control group, in 10m speed tests with and without a ball, 20m single sprint and Illinois agility tests (p < 0.05). Thus 8-weeks performing the 11+ warm-up program can enhance jump height, agility and soccer skill while the HarmoKnee program generally only improves soccer skill in young professional male soccer players.